2019
DOI: 10.9734/ajbgmb/2019/v2i130051
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Chemopreventive Effect of Methanol Extract of Carica papaya Seed on Potassium Bromate- Induced Nephrotoxicity in Rats

Abstract: Aim: To investigate the effect of Carica papaya seed extract on KBrO3 - induced nephrotoxicity in rats. Renal toxicity was induced by a single oral dose of 100 mg/kg body weight of KBrO3. Study Design: Thirty (30) male albino rats were divided into six groups, five rats per group; normal control, KBrO3 control, papaya control and KBrO3 group administered with methanol seed extract of 200 mg/kg, 400 mg/kg and 600 mg/kg body weight for 48 hours. Place and Duration of Study: Department of Biochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Additionally, as HCO 3 and Cl are reabsorbed in the proximal tubule, a high level of these electrolytes may indicate tubular renal damage. This outcome is consistent with the rise in all electrolytes observed by Kanadi et al [55] after exposure of animals to KBrO 3 . The main anion in serum is chloride.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, as HCO 3 and Cl are reabsorbed in the proximal tubule, a high level of these electrolytes may indicate tubular renal damage. This outcome is consistent with the rise in all electrolytes observed by Kanadi et al [55] after exposure of animals to KBrO 3 . The main anion in serum is chloride.…”
Section: Discussionsupporting
confidence: 92%
“…This study's findings agree with those of Akomolafe et al [40] and Abd-Elmaksoud et al [41]. These outcomes could be anticipated as a result of the kidney's failure to do its purification and removal of metabolites functions due to structural changes in the renal tissues following injection of KBrO 3 , as previously documented [8,42].…”
Section: Discussionsupporting
confidence: 91%
“…This result is in harmony with reports of Akomolafe et al [8] and Abd Elmaksoud et al [18] . These results may be expected to the kidney's incapability to carry out its functions of purification and removal of metabolites as a result of the structural alterations in the kidney tissues after administration of KBrO 3 as repotred previously [19] . The kidney is responsible for the management of different electrolytes and the care of homeostasis [20] .…”
Section: Discussionmentioning
confidence: 69%
“…The kidney is responsible for the management of different electrolytes and the care of homeostasis [20] . Sodium (Na + ) and potassium (K + ) are chief components of extracellular and intracellular fluids, respectively, therefore the raised levels of these electrolytes could signify renal dysfunction, mainly at glomerular and tubular levels [19]. The current result showed that KBrO 3 was correlated with a significant increase in serum levels of Na + and K + ions; this agrees with Adewale et al [6] who mentioned that oral ingestion of KBrO 3 alone increased significantly the serum electrolytes "Na + , Cl -, HCO 3 and K + ".…”
Section: Discussionmentioning
confidence: 99%